Effect of CaCl 2 Crosslink Solution Concentration on the Characteristics of Gelatin Alginate Microspheres - Rizka Safitri1, Tutiek Purwanti1, Widji Soeratri1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Alginate as a constituent of microspheres matrix has a weakness, namely the lack of ability to slow the release of drugs from the system, causing the effects of drug therapy to the body to be less than optimal. To obtain preparations with slowed release, sodium alginate needs to be combined with other polymers such as gelatin. This study aims to determine the effect of the concentration of CaCl 2 connection solution on the characteristics of alginate-gelatin microspheres. In this study, alginate-gelatin microspheres were prepared using ionotropic gelation aerosolization techniques. Three formulas were made, each of which was replicated three times. F1 with CaCl concentration2 0.5 M, F2 with CaCl concentration2 1.0 M, F3 with a concentration of 1.5 M. The three formulas were made in the ratio of alginate-gelatin (1.5: 1)% and a crosslinking time of 1.5 hours. Evaluation of the characteristics of microspheres includes yield percentage, organoleptic, moisture content, morphology of microspheres, size and size distribution of microspheres, and swelling index. The data of this study were analyzed using one way ANNOVA. The results reveals a loss of specific uptake of the COO-manuronate alginate group and the occurrence of wave number shifts as well as an increase in the absorption intensity of the C = O group. Organoleptic examination results of alginate-gelatinin microspheres showed that microspheres of the three formulas had the same organoleptic, and formed spherical microspheres. On the inspection of swelling index, it was found that F1 and F2 reached the peak of swelling at 2 o’clock, while F3 reaches the peak of swelling at 3 o’clock. The greater the level of CaCl2, then the average diameter of microspheres will also increase, while the swelling index will decrease with increasing levels of CaCl2. In the results of moisture content examination, there is no difference in different CaCl 2.